Pengaruh Pengalaman Kerja dan Beban kerja terhadap Kinerja Karyawan pada PT. Astra Honda Motor Unaaha - Tauwi Tauwi (Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
The purpose of this study was to determine and analyze the effect of work experience and workload on employee performance at PT. Astra Honda Motor Unaaha. The location of this study was conducted at the showroom of PT. Astra Honda Motor Unaaha, which is located in Tumpas Village, Unaaha District, Konawe Regency. In this study, all populations were sampled, namely 30 employees. To measure the effect of work experience and workload on employee performance, a measuring instrument in the form of a questionnaire was used, the answer categories for questions using the Likert Scale. Work experience and workload have a significant effect on employee performance, this means that the more work experience and balanced workload will increase employee performance, where the partial test of the work experience variable (X1) obtained a t significance of 0.001 smaller than 0.05, then partially the work experience variable (X1) has an effect on employee performance variables (Y). And the partial test on the workload variable (X2) obtained a t significance of 0.000, or a t significance of less than 0.05, so partially the workload variable (X2) has an effect on the employee performance variable (Y).